Damaged-plasticity concrete model identification for prediction the effects of CFRPs on strengthening the weakened RC two-way slabs with central, lateral and corner openings. (2015) - Labibzadeh, Mojtaba
The effects of the lateral and corner openings as well as the impact of using carbon fibre reinforced polymer sheets (CFRPs) on the RC two-way slabs' bearing capacity were investigated. To this end, at first, an enhanced finite element model of an actual laboratory sample of a reinforced concrete slab with central opening was simulated and verified using available experimental results. For concrete behaviour simulation, a sophisticated material model named damaged-plasticity model which can predict well the nonlinear behaviour of concrete from the initial steps of loading scenario up to the failure state was formulated and identified. For verifying the identification, two concrete beam test setup were simulated and the obtained results were compared with the laboratory test results. It was declared that the combined 45 and 90 degrees arrangement of CFRPs can affect more efficiently in strengthening weakened slabs with openings than the other CFRPs arrangements.